Gluten-dependent intestinal autoimmune response. - Korponay-Szabó, Ilma Rita; Simon-Vecsei, Zsafia; De Leo, Luigina; Not, Tarcisio (Curr Pharm Des, 2012)
Celiac disease is a multi-systemic autoimmune disease of the small bowel induced by gluten in genetically predisposed subjects. Highly specific and gluten-dependent production of auto-antibodies targeting self-proteins of the transglutaminase family occurs in the intestinal mucosa. These anti-transglutaminase antibodies are found deposited in intestinal and extra-intestinal tissue where they might exert biological effects, together with the intestinal mucosal gliadin-specific T lymphocytes. We conducted a brief review on antitransglutaminase antibodies effects, discussing their roles in the pathogenesis of several clinical manifestations of celiac disease.
Keywords: Animals; Autoantibodies; Celiac Disease; Genetic Predisposition to Disease; Gliadin; Glutens; Humans; Intestinal Mucosa; T-Lymphocytes; Transglutaminases